Relationship between soil management practices and occurrence of foot rot disease Phytophthora spp. in citrus - Oliveira, Antonio Alberto Rocha; Santos Filho, Hermes Peixoto; Coelho, Ygor da Silva; Passos, Orlando Sampaio; Cunha Sobrinho, Almir Pinto da (Pesquisa Agropecuaria Brasileira, 2014)
In order to study the relationship between different soil management practices and the incidence of citrus fool rot disease, a survey was conducted on a trial at the CNPMF/EMBRAPA, Cruz das Almas county, State of Bahia, Brazil. The mechanical tillage to maintain clean cultivation showed the highest incidence of foot rot disease, probably as a consequence of root damage and trunk injuring. Herbicides as well as control by mowing did not increase the normal level of Phytophthora usually found in this area.